22(R)-hydroxycholesterol for dopaminergic neuronal specification of MSCs and amelioration of Parkinsonian symptoms in rats - Manisha Singh; Manish Jain; Samrat Bose; Ashutosh Halder; Tapas Chandra Nag; Amit Kumar Dinda; Sujata Mohanty (Cell Death Discovery, 2021)
Abstract Oxysterols play vital roles in the human body, ranging from cell cycle regulation and progression to dopaminergic neurogenesis. While naïve human mesenchymal stem cells (hMSCs) have been explored to have neurogenic effect, there is still a grey area to explore their regenerative potential after in vitro differentiation. Hence, in the current study, we have investigated the neurogenic effect of 22(R)-hydroxycholesterol (22-HC) on hMSCs obtained from bone marrow, adipose tissue and dental pulp. Morphological and morphometric analysis revealed physical differentiation of stem cells into neuronal cells. Detailed characterization of differentiated cells affirmed generation of neuronal cells in culture. The percentage of generation of non-DA cells in the culture confirmed selective neurogenic potential of 22-HC. We substantiated the efficacy of these cells in neuro-regeneration by transplanting them into Parkinson’s disease Wistar rat model. MSCs from dental pulp had maximal regenerative effect (with 80.20 ± 1.5% in vitro differentiation efficiency) upon transplantation, as shown by various behavioural examinations and immunohistochemical tests. Subsequential analysis revealed that 22-HC yields a higher percentage of functional DA neurons and has differential effect on various tissue-specific primary human MSCs. 22-HC may be used for treating Parkinson’s disease in future with stem cells.